Retinal Microvascular Changes on OCT-Angiography in Preclinical Alzheimer’s Disease: A Prospective Indonesian Cohort Study - Taufiq Indera Jayadi; Eva Naritawati; Akmal Hasan (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2025)
Introduction: Preclinical Alzheimer’s disease (AD) involves cerebral amyloid deposition in cognitively normal individuals 15–20 years before symptom onset. Optical coherence tomography angiography (OCT-A) may detect early retinal microvascular changes reflecting cerebral pathology. This study evaluated OCT-A parameters as biomarkers for preclinical AD in Indonesian elderly. Methods: This prospective cohort enrolled 180 cognitively normal participants aged ≥60 years (90 preclinical AD with amyloid-PET positivity, 90 controls) at two private hospital ophthalmology clinics in Palembang and Jakarta, Indonesia (January 2022–June 2024). OCT-A (RTVue XR Avanti) measured superficial capillary plexus (SCP) and deep capillary plexus (DCP) vessel density, foveal avascular zone (FAZ) area, and perfusion density. SD-OCT assessed RNFL and GCL-IPL thickness. The unit of analysis was the individual eye (342 eyes after quality exclusion). Results: SCP vessel density was significantly reduced in preclinical AD (43.2 ± 3.1% vs 47.8 ± 2.9%; Bonferroni-adjusted p < 0.001; Cohen’s d = 1.53). FAZ area was enlarged (0.38 ± 0.08 vs 0.31 ± 0.06 mm²; p < 0.001). The combined model (SCP + FAZ + GCL-IPL) achieved a bootstrap-validated AUC of 0.898 (95% CI: 0.859–0.937). SCP vessel density was the strongest predictor (OR 0.72; 95% CI: 0.63–0.82; p < 0.001). Conclusion: OCT-A parameters, particularly SCP vessel density, demonstrated strong discriminative ability for preclinical AD. These findings support OCT-A as a potential non-invasive screening biomarker, warranting validation in community-based populations.